THE ROLE OF SOCIAL SCIENCE LEARNING IN CONSTRUCTING NATIONAL CHARACTERS - Mispondari, Dwi Unggul; Birsyada, Muhammad Iqbal (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2024)
This research aims to find out: To know 1) The role of learning Social Studies History towards the cultivation of character values of love for the homeland in class VIII students of SMP Muhammadiyah 1 Yogyakarta. 2) To find out the function of learning social studies history of the character values of love for the homeland in class VIII students of SMP Muhammadiyah 1 Yogyakarta. 3) To find out how the cultivation of the character values of love for the country in the process of learning social studies. The method used in this research is a qualitative research method case study, techniques in data collection in this study using observation, interviews, documentation, and library research. Data analysis in this study uses data collection procedures, data reduction, data presentation, and data conclusion. Data validity checks in this study used triangulation of techniques and triangulation of sources. The results of this study indicate that Social Studies History subjects have a very important role in the cultivation of character education for the attitude of patriotism towards students, Character Education for patriotism has a role that has many benefits and functions both in the world of education and social society. So that students can understand and apply the attitude of love for the country. The function of Social Science History towards cultivating an attitude of love for the country includes fostering a sense of nationalism towards the state and nation. The process of cultivating an attitude of love for the homeland in learning Social Science History educators can insert important values about the attitude of love for the homeland during the learning process.